Ruthenium-containing P450 inhibitors for dual enzyme inhibition and DNA damage. Issue 7 (25th January 2017) - Zamora, Ana; Denning, Catherine A.; Heidary, David K.; Wachter, Erin; Nease, Leona A.; Ruiz, José; Glazer, Edith C.
Abstract : A light-activated prodrug delivers both a DNA damaging metal center and a cytochrome P450 inhibitor to prevent drug resistance. Abstract : Cytochrome P450s are key players in drug metabolism, and overexpression in tumors is associated with significant resistance to many medicinal agents. Consequently, inhibition of P450s could serve as a strategy to restore drug efficacy. However, the widespread expression of P450s throughout the human body and the critical roles they play in various biosynthetic pathways motivates the development of P450 inhibitors capable of controlled local administration. Ruthenium complexes containing P450 inhibitors as ligands were synthesized in order to develop pro-drugs that can be triggered to release the inhibitors in a spatially and temporally controlled fashion. Upon light activation the compounds release ligands that directly bind and inhibit P450 enzymes, while the ruthenium center is able to directly damage DNA.